2013
DOI: 10.1088/0965-0393/21/6/065001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of anisotropic friction in nanotwinned Cu revealed by atomistic simulations

Abstract: The nature of nanocrystalline materials determines that their deformation at the grain level relies on the orientation of individual grains. In this work, we investigate the anisotropic response of nanotwinned Cu to frictional contacts during nanoscratching by means of molecular dynamics simulations. Nanotwinned Cu samples containing embedded twin boundaries parallel, inclined and perpendicular to scratching surfaces are adopted to address the effects of crystallographic orientation and inclination angle of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 58 publications
(81 reference statements)
1
8
0
Order By: Relevance
“…Figure 3(b) shows the friction coefficient, which is calculated as the ratio of the vertical force over the lateral force, as a function of the scratching length. From this figure, we can see that after the rapid increase in the initial scratching stage, the friction coefficient fluctuates acutely around a certain value in the later stage, which is similar to that observed in the nanoscratch of the conventional NT copper samples containing parallel TBs along the scratching direction (Zhang et al, 2013). The friction coefficient of the current sample is about 0.38, which is higher than those of conventional NT copper samples as studied in Zhang et al (2013).…”
Section: Inelastic Deformation Mechanismssupporting
confidence: 76%
See 1 more Smart Citation
“…Figure 3(b) shows the friction coefficient, which is calculated as the ratio of the vertical force over the lateral force, as a function of the scratching length. From this figure, we can see that after the rapid increase in the initial scratching stage, the friction coefficient fluctuates acutely around a certain value in the later stage, which is similar to that observed in the nanoscratch of the conventional NT copper samples containing parallel TBs along the scratching direction (Zhang et al, 2013). The friction coefficient of the current sample is about 0.38, which is higher than those of conventional NT copper samples as studied in Zhang et al (2013).…”
Section: Inelastic Deformation Mechanismssupporting
confidence: 76%
“…The copper atoms at the bottom are fixed to avoid rigid body motion during indentation and scratch. The simulation procedure and parameters are similar to those adopted in previous studies (Kelchner et al, 1998;Sun et al, 2011;Zhang et al, 2013). The time step utilized in the MD simulations is 2 fs.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…The effects of crystallographic orientation have been addressed by MD through the scratching on a nano-twinned copper workpiece (containing embedded twin boundaries parallel, inclined and perpendicular to scratching surfaces with different twin spacing) [38]. This work showed that the random coupling of crystallographic orientation and twin boundary orientation with respect to the scratching direction strongly influenced the competition between individual deformation mechanisms.…”
Section: Polycrystallinementioning
confidence: 99%
“…Brown et al showed that the plasticity in twinned Cu nanopillars greatly depends on the TBs’ orientation with respect to the loading axis [ 10 ]. Zhang et al investigated the effect of the inclination angle on the nanoscratching behavior of nanotwinned copper, and found a critical inclination angle of 26.6° for the lowest yield strength and the highest friction coefficient [ 11 ]. However, there is rather limited work focusing on the effect of the inclination angle of TBs on the mechanical properties of aluminum.…”
Section: Introductionmentioning
confidence: 99%